2021
DOI: 10.21203/rs.3.rs-604840/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Globular pattern formation of hierarchical ceria nanoarchitecture

Abstract: Dissipative structures often appear as an unstable counterpart of ordered structures owing to fluctuations that do not form a homogeneous phase. Even a multiphase mixture may simultaneously undergo one chemical reaction near equilibrium and another one that is far from equilibrium. Here, we observed in real time crystal seed formation and simultaneous nanocrystal aggregation proceeding from CeIV complexes to CeO2 nanoparticles in an acidic aqueous solution, and investigated the resultant hierarchical nanoarchi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
(62 reference statements)
0
1
0
Order By: Relevance
“…These studies showed via SAXS and TEM imaging that initially primary particles form (∼1–3 nm diameter), followed by aggregation of these into larger particles (20–30 nm) . A follow-on study by Aoyagi et al confirmed that precipitated CeO 2 nanoparticles are actually aggregates of smaller particles, which suggests high surface areas and pore volumes could be obtained from this very simple chemistry, where such topologies could promote Ce III accompanied by oxygen vacancies. In other studies, nano-CeO 2 (NC-CeO 2 ) was also formed from CAN by adding base and by hydrothermal or solvothermal treatment respectively of aqueous and organic solutions. , Equivalent to adding base, Pettinger et al found that low concentration of CAN spontaneously forms colloidal NC-CeO 2 at room temperature .…”
Section: Introductionmentioning
confidence: 97%
“…These studies showed via SAXS and TEM imaging that initially primary particles form (∼1–3 nm diameter), followed by aggregation of these into larger particles (20–30 nm) . A follow-on study by Aoyagi et al confirmed that precipitated CeO 2 nanoparticles are actually aggregates of smaller particles, which suggests high surface areas and pore volumes could be obtained from this very simple chemistry, where such topologies could promote Ce III accompanied by oxygen vacancies. In other studies, nano-CeO 2 (NC-CeO 2 ) was also formed from CAN by adding base and by hydrothermal or solvothermal treatment respectively of aqueous and organic solutions. , Equivalent to adding base, Pettinger et al found that low concentration of CAN spontaneously forms colloidal NC-CeO 2 at room temperature .…”
Section: Introductionmentioning
confidence: 97%